2009
DOI: 10.1080/17450390903020455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylanase on apparent ileal and total tract digestibility of nutrients and energy of rye in young pigs

Abstract: A digestibility experiment was carried out on weanling piglets to study the effect of an enzyme complex with predominant xylanase activity on apparent ileal (AID) and apparent total tract digestibility of nutrients and energy. The enzyme was supplemented at four levels (0, 50, 100 and 200 mg/kg) to a diet containing 96% rye. There were significant effects of the added enzyme on AID of dry matter, organic matter and crude fibre, and on apparent total tract digestibility of dry matter, organic matter and energy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Several studies in monogastric animals report that the energy in rye is less available and/or energy intake is lower, as shown by a lower growth, lower body weight and reduced adiposity Nitrayova et al, 2009;Pettersson & Åman, 1989;Pettersson & Åman, 1988). The results presented in this thesis showed that a diet with high-fibre rye breads increased the amounts of macronutrients and energy reaching the terminal ileum.…”
Section: Rye For a Healthy Body Weight?supporting
confidence: 56%
See 1 more Smart Citation
“…Several studies in monogastric animals report that the energy in rye is less available and/or energy intake is lower, as shown by a lower growth, lower body weight and reduced adiposity Nitrayova et al, 2009;Pettersson & Åman, 1989;Pettersson & Åman, 1988). The results presented in this thesis showed that a diet with high-fibre rye breads increased the amounts of macronutrients and energy reaching the terminal ileum.…”
Section: Rye For a Healthy Body Weight?supporting
confidence: 56%
“…Furthermore gastric distension, gastric emptying rate and hormonal effects relating to variations in digestion and absorption are likely to play an important role. An intact botanical structure of cereal grains can also lower the digestibility (Nitrayova et al, 2009;Pettersson & Åman, 1989) and result in more material being available for colonic fermentation, suggested to influence satiety (Cani et al, 2009;Zhou et al, 2008). Increased fullness (120-270 min) after intake of rye kernels compared with the whole-grain rye flour bread Bread with 80% wheat kernels, 133 g Bread with 80% whole-grain wheat flour, 108 g 120 min n = 13…”
Section: Food Structurementioning
confidence: 99%
“…Some of these compounds are present as part of the cell wall, thus shielding substrates from contact with the digestive enzymes, or as part of cell content where their presence may interfere with digestion and absorption by their chemical nature. Nitrayová et al (2009) reported improved ileal disappearance of non starch polysaccharides in diets containing 96% rye for weanling swine; there was a 740% improvement in disappearance for xylose and a 144% improvement in disappearance for total non starch polysaccharides when xylanase was added at the rate of up to 200 mg/kg. These data indicate that non starch polysaccharides removal is one of the critical roles of carbohydrases when added to diets containing non starch polysaccharides.…”
Section: Effect Of Carbohydrases On Non Starch Polysaccharidesmentioning
confidence: 97%
“…In fish, the presence of digestive enzymes that specifically hydrolyze the β-glycosidic bonds of NSP seems to be very low or nonexistent (Krogdahl et al, 2005;NRC, 2011). Some of these NSP are present as part of the cell wall, thus shielding substrates from contact with the digestive enzymes, or as part of cell content where their presence may interfere with digestion and absorption due to their chemical nature (Bach-Knudsen, 1997;Nitrayová et al, 2009). The classification of NSP found in commonly used plant feedstuffs for aquaculture feeds is presented in Table 1.…”
Section: Non-starch Polysaccharides and Mechanisms Of Action Of Carbomentioning
confidence: 99%